Prevalence and determinants of contraceptive utilization among married women at Dabat Health and Demographic Surveillance System site, northwest Ethiopia - Geta Asrade Alemayehu; Abel Fekadu; Mezgebu Yitayal; Yigzaw Kebede; Solomon Mekonnen Abebe; Tadesse Awoke Ayele; Zemichael Gizaw; Mamo Wubeshet; Kindie Fentahun Muchie; Abebaw Addis Gelagay; Temesgen Azmeraw; Melkamu Birku; et al. (BMC, 2018)
Abstract Background Despite the enormous benefits of family planning services, the contraceptive utilization still remains low in Sub-Saharan Africa. There is regional variation in modern contraceptive utilization in Ethiopia. Therefore, this study was aimed to determine the prevalence of modern contraceptive utilization and determinants in Dabat demographic and health surveillance system site, northwest Ethiopia. Methods A re-census was carried out in Dabat Health and Demographic Surveillance System (HDSS) site from October to December 2014. Data of 8271 married women collected in the re-census was used. The outcome variable was current utilization of any modern contraceptive methods whereas socio demographic and economic variables were the potential determinants considered. Bi-variable and multivariable binary logistic regression along with odds ratio and 95% confidence interval were used to describe the strength of association. Results Prevalence of modern contraceptive utilization among married women in Dabat DHSS site was found to be 32.5% (95%CI: 31.5, 33.5%). After adjusting for covariates; the odds of using modern contraceptive were 2.35 times, 1.91 times, and 1.39 times higher among women of secondary and above educational level, urban residents, and women having six and above living children, respectively. Conclusion Modern contraceptive utilization was found to be very low. Effort has to be applied to improve women's educational level that increases their understanding of reproductive health issues. It is also important to give special emphasis for rural residents, those aged 20-40 years, and those with six or more living children while serving for modern contraceptive methods.